2016
DOI: 10.1007/s00705-016-2774-2
|View full text |Cite
|
Sign up to set email alerts
|

One-step reverse transcription loop-mediated isothermal amplification (RT-LAMP) for detection of tomato torrado virus

Abstract: ‘Torrado’ disease caused by tomato torrado virus (ToTV) is responsible for considerable losses in tomato production. Therefore, a one-step reverse transcription loop-mediated isothermal amplification protocol for early and fast detection of ToTV isolates has been developed. The RNA extracted from ToTV-infected plants was tested using this protocol with a set of six primers specific for the Vp35 coat protein gene sequence. The amplified products were analyzed using amplification curves, electrophoresis, and dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
3
13
0
1
Order By: Relevance
“…However, the detection limit of the conventional PCR (20 pg RNA). These results are in line with those of previous studies 20 24 . Interestingly, the current assay is more sensitive than the previously reported one 16 .…”
Section: Discussionsupporting
confidence: 94%
“…However, the detection limit of the conventional PCR (20 pg RNA). These results are in line with those of previous studies 20 24 . Interestingly, the current assay is more sensitive than the previously reported one 16 .…”
Section: Discussionsupporting
confidence: 94%
“…Generally, four to six primers are designed that recognize several regions of the target sequence, which gives high specificity in LAMP assay. Recently, LAMP assay been applied to the rapid detection of tomato torrado virus in tomato [2]. Several workers found that LAMP shows more sensitive than quantitative real-time PCR assays [19,21,25].…”
Section: Introductionmentioning
confidence: 99%
“…These primers hybridize with the stem-loops, with an exception of the loops hybridized by the inner primers and prime strand displacement DNA synthesis [24]. Currently, six primers are widely used in many diagnostic protocols to allow better specificity and sensitivity [30][31][32].…”
Section: Lamp Accelerationmentioning
confidence: 99%